1995
DOI: 10.1080/00049539508258763
|View full text |Cite
|
Sign up to set email alerts
|

Implicit learning: Sensitive to age but not IQ

Abstract: According to Reber (1992), implicit learning should vary only minimally with age and intelligence quotient (IQ), whereas explicit learning should depend heavily on both age and IQ. To evaluate these predictions, children from two age groups (5–7 yean and 10–12 years) were selected to form low, medium, and high IQ subgroups. They were then tested on an implicit and an explicit learning task. The implicit task, adapted from Lewicki (1986), used a number of 4 × 4 matrices which displayed 16 pictures in different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
67
2
5

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(82 citation statements)
references
References 34 publications
6
67
2
5
Order By: Relevance
“…While the majority of previous research suggests that there is little development of implicit learning across childhood (e.g., Don, Schellenberg, Reber, DiGirolamo, & Wang, 2003;Meulemans et al, 1998;Thomas & Nelson, 2001;Thomas et al, 2004), there have been a few implicit learning studies that have suggested developmental differences (Maybery, Taylor, & O'Brien-Malone, 1995;Thomas & Nelson, 2001;Thomas et al, 2004;Vaidya et al, 2007). Thus, in the experiments presented in this study it is possible that developing implicit learning is contributing to overall learning.…”
Section: Discussionmentioning
confidence: 55%
“…While the majority of previous research suggests that there is little development of implicit learning across childhood (e.g., Don, Schellenberg, Reber, DiGirolamo, & Wang, 2003;Meulemans et al, 1998;Thomas & Nelson, 2001;Thomas et al, 2004), there have been a few implicit learning studies that have suggested developmental differences (Maybery, Taylor, & O'Brien-Malone, 1995;Thomas & Nelson, 2001;Thomas et al, 2004;Vaidya et al, 2007). Thus, in the experiments presented in this study it is possible that developing implicit learning is contributing to overall learning.…”
Section: Discussionmentioning
confidence: 55%
“…Age differences should thus be observed in observationalmotor implicit learning. In support of this hypothesis, it is worth pointing out that the single study reporting a deficit in children compared with adults in an implicit learning task used a task based on perceptual judgments without motor involvement (Maybery, Taylor, & O'Brien-Malone, 1995).…”
Section: -Accepted By Previous Editorial Teammentioning
confidence: 92%
“…First, it has been demonstrated that this kind of learning is based on processes that remain unaffected by developmental differences and, thus, is perfectly efficient in preschoolers (Meulemans, Van der Linden, & Perruchet, 1998;Vinter & Perruchet, 2000; but see Maybery, Taylor, & O'Brien-Malone, 1995). Second, the studies evoked above indicate that people can become sensitive to subtle environmental regularities such as frequent co-occurrences and perhaps syntactic rules.…”
Section: Introductionmentioning
confidence: 99%